The angiotensin converting enzyme I/D polymorphism in Russian athletes - Nazarov, I. B.; Woods, D. R.; Montgomery, H. E.; Shneider, O. V.; Kazakov, V. I.; Tomilin, N.; Rogozkin, V. A. (European Journal of Human Genetics, 2001)
The deletion (D) allele of the human ACE gene is associated with higher ACE activity than the insertion (I) allele. There is controversy as to whether the ACE genotype may be associated with elite athletic status; recent studies have identified no significant associations amongst those drawn from mixed sporting disciplines. However, such lack of association may reflect the mixed nature of such cohorts, given that an excess frequency of the I allele has been reported amongst elite endurance athletes, and an excess of the D allele amongst those engaged in more power-orientated sports. We examined this hypothesis by determining ACE I/D allele frequency amongst 217 Russian athletes (swimmers, skiers, triathletes and track-and-field participants) prospectively stratified by performance ('outstanding' or 'average'), and the duration of their event (SDA (<1 min), MDA (1 to 20 min), and LDA (>20 min): short, middle and long distance athletes respectively). ACE genotype and allele frequencies were compared to 449 controls. ACE genotype frequency amongst the whole cohort, or the outstanding athletes alone, was no different to that amongst sedentary controls. However, there was an excess of the D allele (frequency 0.72, P=0.001) amongst the outstanding SDA group, and an excess of the I allele (frequency 0.63, P=0.032) amongst the outstanding MDA group. These findings were replicated in the outstanding swimmers, with track and field SDA similarly demonstrating an excess of the D allele (P=0.01). There was no association found between the outstanding LDA and ACE genotype (P=0.27). These data not only confirm an excess of the D allele in elite SDA, and I allele in elite MDA, but also offer an explanation as to why any such association may be hard to detect amongst a heterogeneous cohort of mixed athletic ability and discipline.